Intraocular correction of presbyopia in cataract surgery - A. Zh. Fursova; A. A. Atamanenko; F. K. Rabota; E. I. Dmitrieva (Российский офтальмологический журнал)
Cataract is one of the leading causes of blindness worldwide; its prevalence increases with age, ranging from 3.9 % among 55–64 years old to 92.6 % among those aged 80 years or more. Intraocular lenses (IOLs) are used in cataract surgery to replace the natural human lens and/or correct refractive errors. In recent years, a wide range of IOLs have been developed for the correction of presbyopia, which have surpassed traditional monofocal intraocular lenses. With an increased life duration and lifestyle changes, an increasing number of patients are not content with excellent distant vision alone but wish to have adequate near- and intermediate-distance vision. The review presents modern approaches to the correction of presbyopia by IOLs produced with the help of various technologies. The mechanisms of presbyopia correction, the general principles of multifocal IOL use, extended depth of focus (EDOF) technology, the advantages and drawbacks of individual IOL categories such as multifocal IOLs, improved monofocal IOLs, and deep focus IOLs are discussed. Special attention is given to terminology. Specifically, the concepts of EDOF and multifocal IOLs are distinguished, which however are not mutually exclusive as bifocal IOL, aspherical monofocal IOL, diffraction or refraction trifocal IOL can have EDOF characteristics (with partial range limitation at near distance in order to minimize dysphotoptic complaints). Taking into account the active marketing strategies of IOL manufacturers, the presented data can be useful in clinical practice, facilitating and structuring the relevant information for the ophthalmologist. Innovative solutions in the development of materials, optical platforms and the design of intraocular lenses for intraocular presbyopia correction provide a differentiated approach to achieving high functional results depending on the individual needs of patients.